Association between polyunsaturated fatty acids dietary intake and pulmonary function among American children: NHANES 2007–2012 - Ding, Mengmeng; Qie, Shuyan; Wang, Hanming (Frontiers in Nutrition, 2025)
BackgroundThe existing evidence regarding the protective effect of polyunsaturated fatty acids (PUFAs) on pulmonary function remains a subject of considerable controversy. Based on this, we further investigated the correlation of PUFAs intake in diet with pulmonary function in healthy American children.MethodsA cross-sectional survey was conducted using the National Health and Nutrition Examination Survey (NHANES) database of children aged 6–17 in the United States from 2007 to 2012. The correlation of PUFAs intake in diet with pulmonary function was investigated through weighted multivariate linear regression and restricted cubic spline (RCS) curve visualization analysis. Subgroup analysis was carried out to further investigate the robustness of the results and potential interactions in terms of gender, race, age of child, age of mother at birth, and poverty-income ratio (PIR).ResultsAltogether 2,508 participants were enrolled in this research. After adjusting for confounders, PUFAs intake was positively correlated with forced expiratory volume in 1 s (FEV1) (β = 7.525; 95%CI: 2.935–12.12; p = 0.002) and FVC (β = 9.138; 95%CI: 4.389, 13.89; P < 0.001). The modeling of PUFAs subtypes revealed that FEV1 and FVC increased with increasing intake of omega-3 and omega-6 (p < 0.01). The RCS results showed a non-linear relationship (p < 0.001) of PUFAs and omega-6 with FEV1 and FVC. A subgroup analysis in this research revealed an interaction of PUFAs intake with the gender of children, with PUFAs having a better protective effect on pulmonary function in males than in females (FEV1: p = 0.017; FVC: p = 0.022).ConclusionThe total intake of PUFAs in the diet was positively correlated with pulmonary function in children in the United States, and this correlation was more significant in the male population. The results of this study further confirmed that dietary supplementation of PUFAs was beneficial for improving pulmonary function in children.